2009
DOI: 10.1007/s10750-009-9743-7
|View full text |Cite
|
Sign up to set email alerts
|

Dietary flexibility in three representative waterbirds across salinity and depth gradients in salt ponds of San Francisco Bay

Abstract: Salt evaporation ponds have existed in San Francisco Bay, California, for more than a century. In the past decade, most of the salt ponds have been retired from production and purchased for resource conservation with a focus on tidal marsh restoration. However, large numbers of waterbirds are found in salt ponds, especially during migration and wintering periods. The value of these hypersaline wetlands for waterbirds is not well understood, including how different avian foraging guilds use invertebrate prey re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Tracing seasonal variations in habitat use within a heterogeneous wetland complex using traditional approaches is almost impossible (but see González Solís et al, 1997;Votier et al, 2003;Takekawa et al, 2009). Several interacting factors mediate seasonal patterns of habitat use in waterbirds.…”
Section: Discussionmentioning
confidence: 99%
“…Tracing seasonal variations in habitat use within a heterogeneous wetland complex using traditional approaches is almost impossible (but see González Solís et al, 1997;Votier et al, 2003;Takekawa et al, 2009). Several interacting factors mediate seasonal patterns of habitat use in waterbirds.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the areas of low marshes, channels, and upland edges are dominated by Spartina foliosa, which is favored by clapper rail because it can provide sufficient food sources, shelter from predators and tides, and nesting substrate (Spautz and McBroomand, 2006). Studies on salt ponds in the Estuary (Takekawa et al, 2006(Takekawa et al, , 2009) also indicate that salinity is highly correlated with Fig. 7.…”
Section: Analysis Of Dominant Factors In Habitat Quality Evaluationmentioning
confidence: 83%
“…We chose a 10-m × 10-m grid size to sample habitat at a scale appropriate to (1) the size of the habitat features of interest and (2) the spatial resolution of the bird location data, which were mapped based on a visual estimation of their position in the unit by the surveyor in the field. Previous research has shown that water depth is a significant driver of bird use of managed wetlands, with deeper areas mostly unavailable to wading birds (Elphick and Oring 1998;Isola et al 2000;Takekawa et al 2009). However, because we lacked detailed topographic data for 87 pond bottoms, we could not directly incorporate water depth in our evaluation of habitat use.…”
Section: Waterbird Space Use In Relation To Habitat Features 2019mentioning
confidence: 99%
“…For example, foraging Forster's Terns have been observed in both managed ponds and tidal marshes, but by far the largest percentage of foraging locations were in managed ponds, especially lower-salinity ponds (Ackerman et al https://doi.org/10.15447/sfews.2023v21iss2art2 2008; Bluso- Demers et al 2016). American Avocets typically forage in the shallow areas at pond edges and are able to exploit prey in both high-and lowsalinity ponds (Ackerman et al 2007;Takekawa et al 2009;Demers et al 2010). Several studies have emphasized the importance for nesting waterbirds of islands within managed ponds (Strong et al 2004a;, and Black-necked Stilts are known to use more vegetated micro-habitat for nesting than American Avocets .…”
Section: Introductionmentioning
confidence: 99%